The Efficacy of Melatonin, Clonidine and Gabapentin in Reducing Preoperative Anxiety and Postoperative Pain in Patients Undergoing Laparoscopic Cholecystectomy: A Randomized Clinical Trial - Vahide Sadat Hosseini; Reza Atef Yekta; Shaqayeq Marashi; Seyed Mojtaba Marashi (Archives of Anesthesia and Critical Care, 2015)
Background: We performed this study to evaluate the efficacy of melatonin, clonidine and gabapentin in reducing preoperative anxiety and postoperative pain in patients undergoing laparoscopic cholecystectomy. Methods: This study was a randomized clinical trial on patients scheduled for laparoscopic cholecystectomy. A total number of 88 patients were categorized into four groups to receive melatonin, clonidine, gabapentin and placebo (22 patients per group). The anxiety level was evaluated by State-Train Anxiety Inventory (STAI) just before the entrance of patients into the operating room. The intensity of pain was determined according to standard VAS (Visual Analog Scale) criteria for pain assessment at 1, 2, 6, 12 and 24 hours after surgery. The times of receiving the first dose of morphine and also total amount of administered morphine during first 24 hours after surgery were documented. The frequency of vomiting episodes and the intensity of post-operative nausea and vomiting (PONV) during first 24 hours after surgery were recorded according to the VAS criteria. Results: Regarding age, gender, weight, height, systolic blood pressure, diastolic blood pressure and heart rate, no significant differences were noted between the treatment groups. Also regarding the state-trait anxiety score, there were no significant differences between treatment groups (P=0.27). The pain intensity was different between groups (p<0.01); as the placebo group had the highest score; however paired comparison between intervention groups did not show significant differences. The intensity of pain was significantly decreased by the time (P<0.01) and depending on the assigned group, the pain reduction trend was different among treatment groups (P<0.01). In general, the clonidine group had the least pain score in different time periods. Conclusion: Use of melatonin as a premedication had the efficacy similar to the efficacy of clonidine and gabapentin in reducing preoperative anxiety, postoperative pain and also reducing narcotic consumption.